Effectiveness of nicotine replacement therapy sample at outdoor smoking hotspots for initiating quit attempts and use of smoking cessation services: a protocol for a cluster randomised controlled trial - William Ho Cheung Li; Tai Hing Lam; Yee Tak Derek Cheung; Ching Han Helen Chan; Kin Sang Ho; Celeste Tang; Chloe Wing Hei Lau (BMJ Open, 2020)
Introduction More than half of the smoking population in Hong Kong are unmotivated to quit. Only about 2% of tobacco users in the territory have ever used cessation aids such as nicotine replacement therapy (NRT). The present study aims to assess the effectiveness of delivering 1-week free NRT sample plus brief intervention to smokers at outdoor smoking hotspots on quit attempts and use of smoking cessation services.Methods and analysis This is a two-arm, pragmatic, multisite, cluster randomised controlled trial (RCT) on the effectiveness of increasing quit attempts, use of cessation service and recruitment outcomes. Trained smoking cessation ambassadors will approach smokers at outdoor smoking hotspots, and deliver brief smoking cessation advice. Recruitment sessions are randomised to intervention or control group (allocation ratio 1:1). Participants in the intervention group (n=550) will receive 1-week free NRT sample (either patch or gum), brief medication advice from an onsite nurse and cessation service referral, whereas participants in control group (n=275) will only receive the brief advice and service referral. The primary outcomes are the proportion of participants who enrol in any cessation service in Hong Kong within 1 month of the recruitment, and the proportion of participants who report quit attempts at 1-month follow-up. Secondary outcomes include self-reported use of NRT, self-reported 7-day tobacco abstinence, 30-day abstinence at 3 months and 6 months, biochemically validated abstinence at 6 months, perceived importance, difficulty and confidence to quit (scale 0–10), and Incremental Behavior Change towards Smoking Cessation. Process outcomes include number of smokers who will be approached, will accept the brief smoking cessation advice or be recruited to participate in the RCT.Ethics and dissemination The Institutional Review Board of the University of Hong Kong/Hospital Authority Hong Kong West Cluster approved the trial (UW 18-118). Findings will be disseminated through funding website, publication and conference presentations.Trial registration number NCT03717051